Coaching supervision advancing practice and changing landscapes - Birch, Jo 1957-; Welch, Peter 1950- (Routledge-EMCC Masters in Coaching and Mentoring, 2019)
This book will be popular with experienced professionals who want to stretch and deepen their practice, keep up-to-date with current studies, challenge and catalyse their own thinking, and embrace learning from real-world practitioner examples and applied research